The use of LYVE-1 antibody for detecting lymphatic involvement in patients with malignant melanoma of known sentinel node status. Issue 7 (23rd June 2005) - Sahni, D; Robson, A; Orchard, G; Szydlo, R; Evans, A V; Russell-Jones, R
Abstract : Background: Sentinel node (SN) status is the most important prognostic indicator in patients with cutaneous melanoma without clinically evident metastatic spread, but the procedure is associated with considerable morbidity. The LYVE-1 lymphatic marker offers the possibility of studying lymphangiogenesis and tumour metastasis within the primary excision. Aims: To establish whether lymphatic vessel numbers/distribution within the primary tumour correlated with SN status. To assess whether tumour cells were easily demonstrable within lymphatics and could be used as a surrogate for SN status. Methods: Double immunostaining for LYVE-1 and S100 in cutaneous biopsies from 18 SN+ patients with no lymphatic/vascular involvement on routine histology and 18 SN− patients matched for tumour thickness and ulceration. Results: Lymphatic vessels were detected in all cases. Vessels within the tumour mass were suggestive of active lymphangiogenesis; those outside were mainly mature vessels with well defined walls. Tumour cells within lymphatics were detected in one of 18 SN− and five of 18 SN+ patients. Lymphatics containing tumour cells were all outside the tumour mass in well formed vessels, suggesting melanoma cell invasion into preformed lymphatics. There was no significant difference in lymphatic counts between SN+ and SN− patients. Although peritumorous lymphatic counts were higher in ulcerated than non-ulcerated melanomas, they did not vary with Breslow thickness. Conclusion: LYVE-1 staining can reliably demonstrate lymphatic vessel distribution, but lymphatic counts cannot predict melanoma metastatic potential and cannot substitute for SN biopsy. LYVE-1 immunostaining can detect melanoma cells within lymphatics, but is unreliable in predicting melanoma metastasis, failing to detect metastatic spread in more than two thirds of patients with regional node metastasis.